Quo Vadis Masyarakat Pancasila Pengguna Teknologi? - Samson Ganda J. Silitonga (CV. Syntax Corporation Indonesia, 2022)
If Indonesia experienced 2x Communist rebellions (1948 and 1965), then during the first 20 years this country did experience acute ideological problems, and continued until 1992. The ideological problems were never finished after the 1998 Reformasi, although on a different spectrum. In a changing situation, Indonesia may experience the same problem. And if so, what conditions are most likely to make a difference? What is the impact on technology use? Indonesia already has the Pancasila ideology which was formulated by the founding fathers of the country. Ideology comes from layers of national character, as well as a mixture of international ideologies. But what are the consequences for a country of this size? In a pragmatic view, Pancasila is a strategy of social and economic gain. But if Pancasila does not become an authentic value and lifestyle, Pancasila is no more important than the religion embraced by the Indonesian people, even if the religion in question can be socially internalized. Various possibilities must be explored; Pancasila remains relevant in the life of the Indonesian nation. Especially in the use of technology that is getting stronger. There has never been a research article like this that connects global ideology with national ideology, as well as history at the macro and micro levels. At the level of analysis, there has also never been a research article looking at social change with empirical ideological values. Thus, the specificity of this research is to summarize various aspects of ideological issues, as well as the challenges facing technology issues.